Clustering National Open Science and Open Access Policies: A Comparative Analysis of the Research Ethics Standards of European Countries - Artem Artyukhov; Nadiia Artyukhova; Dmytro Chumachenko; Jan Krmela (Business Ethics and Leadership, 2025)

(untitled)
In recent years, Open Science (OS) and Open Access (OA) have become integral to European research policy, driven by the need for greater transparency, accessibility, and collaboration in knowledge production. Despite growing support from the European Commission and other supranational actors, national-level implementation remains fragmented and uneven across the continent. This study aims to compare the development and enforcement of OS&OA policies across 29 European countries and to identify clusters of nations with similar policy profiles. To achieve this, 15 binary and ordinal indicators were compiled from public datasets and policy reports. Using hierarchical clustering based on Manhattan distance and Ward’s D2 linkage, countries were grouped into three distinct clusters. Supporting analyses included descriptive statistics, PCA, and radar plot visualisation. The results show a high clustering tendency (Hopkins H = 0.988) and reveal three meaningful groups: (1) countries with limited or symbolic engagement in OS&OA (e.g., Italy, Ireland); (2) moderate adopters with partial institutionalisation (e.g., France, Czech Republic); and (3) leaders with comprehensive, formalised frameworks (e.g., Netherlands, Germany, Spain). Cluster 3 countries fully include FAIR principles, citizen science, and national mandates, while Cluster 1 countries largely lack these advanced elements. These findings underline the structural disparities in OS&OA policy maturity across Europe and support tailored policy support, peer-learning initiatives, and regional alignment efforts within the European Research Area.